The role of inflammatory response and metabolic reprogramming in sepsis-associated acute kidney injury: mechanistic insights and therapeutic potential - Liu, An-Bu; Tan, Bin; Yang, Ping; Tian, Na; Li, Jin-Kui; Wang, Si-Cong; Yang, Li-Shan; Ma, Lei; Zhang, Jun-Fei (Frontiers in Immunology, 2024)
Sepsis represents a severe condition characterized by organ dysfunction resulting from a dysregulated host response to infection. Among the organs affected, the kidneys are particularly vulnerable, with significant functional impairment that markedly elevates mortality rates. Previous researches have highlighted that both inflammatory response dysregulation and metabolic reprogramming are crucial in the onset and progression of sepsis associated acute kidney injury (SA-AKI), making these processes potential targets for innovative therapies. This study aims to elucidate the pathophysiological mechanisms of renal injury in sepsis by perspective of inflammatory response dysregulation, with particular emphasis on pyroptosis, necroptosis, autophagy, and ferroptosis. Furthermore, it will incorporate insights into metabolic reprogramming to provide a detailed analysis of the mechanisms driving SA-AKI and explore potential targeted therapeutic strategies, providing solid theoretical framework for the development of targeted therapies for SA-AKI.